Application of Scientific Based Modules to Improve High Order Cognitive Skills and Self Efficacy of Learners on Circulation System Material - Hilwah Nora; Andi Ulfa Tenri Pada; Cut Nurmaliah; Muhibbuddin Muhibbuddin; Safrida Safrida (Postgraduate, University of Mataram, 2023)
Students who are at a higher level such as high school should already have higher knowledge or known as High Order Cognitive Skills (HOCS). Within the scope of education, self-efficacy is very important because it can affect cognitive processes, motivation, actions and student achievement. This study aims to determine the differences in high order cognitive skills and self-efficacy in the experimental and control classes. This research is quantitative through a Quasi-Experimental design with a Non-randomized control group, pretest-posttest design. Sampling used a purposive sampling technique with a total sample of 124 students who were divided into two groups, namely the control group and the experimental group. The instrument used to measure HOCS uses multiple choice questions of 40 test questions while self-efficacy is measured using a self-efficacy questionnaire. Data analysis used Ancova at a significance level of 0.05. The results showed that there were differences in the increase in high order cognitive skills and there were differences in students' self-efficacy on circulation system material in class XI after implementing scientific-based modules. The conclusion from this study is that scientific-based modules can be applied to improve students' high order cognitive skills and self-efficacy in circulation system material.